The role of ecological groups in the formation of cyanobacterial communities in the ecosystems of the North Azov region (Ukraine) - A. M. Solonenko; L. I. Arabadzhy-Tipenko; O. M. Kunakh; D. V. Kovalenko (Biosystems Diversity, 2020)
The role of Cyanoprokaryota ecological groups in the ecosystems of the North Azov region was revealed in this work. On the territory of Pryazovskyi National Nature Park, 9 experimental polygons were studied, which covered steppe areas or slopes, salt marshes, coastal sandy soils and water bodies (rivers, lakes, estuaries, sea bays, lagoons). As a result of research on the territory of Pryazovskyi National Nature Park, 124 species of cyanoprokaryotes were identified, which include 127 intraspecific taxa. It was proved that the procedure of canonical correspondence analysis is the most suitable for the analysis of the species matrix. The axes identified as a result of the ordination procedure, which indicate the coordinated dynamics of the species, correlated with both synecological characteristics, such as diversity indicators, and with autoecological characteristics, such as ecotypes of cyanoprokaryotes in relation to habitat types or types of adaptation to salinity conditions. The first four canonical axes together explain 47.5% of species matrix variability. Canonical axis 1 explains 18.0% of the variability of the species matrix and is mostly marked by aqual subaerophytes and eurybionts. This axis indicates the presence of a gradient of salinity conditions where the most saline conditions correspond to the positive values of the axis, and the negative values correspond to less saline. Canonical axis 2 describes 12.1% of species matrix variability. This axis differentiates aquatic ecosystems from others. Canonical axis 3 explains 10.0% of the communities’ variability. This axis distinguishes freshwater ecosystems from saline ecosystems. Markers of freshwater communities are stenotopic halotolerants, which are narrow-range, common mainly in the temperate zone of Europe. The canonical axis 4 explains 7.3% of variability of the matrix of species and is able to differentiate sand ecosystems. The ecotopic structure and geographic range width of community species have the greatest independent value among the considered sources of variation. The independent role of adaptation to the salinity conditions of the ecotope and the role of the type of ecosystems is somewhat smaller. The interaction between the sources of variation is important in the variation of the structure of communities. The interaction between the ecotopic structure and the geographic range width of species and the triple interaction between the ecotopic structure of a community, the width of the geographic range of species and the ecosystem type plays the greatest role in the variation of community structure. Ecotopic groups, which indicate the preference of a particular habitat, correlate with the species composition of the communities. It is shown that the ratio of ecototopic groups in a community is a characteristic that reveals the features of the community as a whole.